Macroscopic X-ray Powder Diffraction Scanning: Possibilities for Quantitative and Depth-Selective Parchment Analysis - Vanmeert, Frederik; De Nolf, Wout; Dik, Joris; Janssens, Koen (Analytical chemistry (Washington), 2018)
At or below the surface of painted works of art, valuable information is present that provides insights into an object's past, such as the artist's technique and the creative process that was followed or its conservation history but also on its current state of preservation. Various noninvasive techniques have been developed over the past 2 decades that can probe this information either locally (via point analysis) or on a macroscopic scale (e.g., full-field imaging and raster scanning). Recently macroscopic X-ray powder diffraction (MA-XRPD) mapping using laboratory X-ray sources was developed. This method can visualize highly specific chemical distributions at the macroscale (dm ). In this work we demonstrate the synergy between the quantitative aspects of powder diffraction and the noninvasive scanning capability of MA-XRPD highlighting the potential of the method to reveal new types of information. Quantitative data derived from a 15th/16th century illuminated sheet of parchment revealed three lead white pigments with different hydrocerussite-cerussite compositions in specific pictorial elements, while quantification analysis of impurities in the blue azurite pigment revealed two distinct azurite types: one rich in barite and one in quartz. Furthermore, on the same artifact, the depth-selective possibilities of the method that stem from an exploitation of the shift of the measured diffraction peaks with respect to reference data are highlighted. The influence of different experimental parameters on the depth-selective analysis results is briefly discussed. Promising stratigraphic information could be obtained, even though the analysis is hampered by not completely understood variations in the unit cell dimensions of the crystalline pigment phases.